2016
DOI: 10.1016/j.rboe.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Congenital dislocation of the patella – clinical case

Abstract: Congenital patellar dislocation is a rare condition in which the patella is permanently dislocated and cannot be reduced manually. The patella develops normally as a sesamoid bone of the femur. This congenital dislocation results from failure of the internal rotation of the myotome that forms the femur, quadriceps muscle and extensor apparatus. It usually manifests immediately after birth, although in some rare cases, the diagnosis may be delayed until adolescence or adulthood. Early diagnosis is important, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Congenital dislocation of the patella is associated with arthrogryposis, chondrodysplasia punctata, dyschondrosteosis, chondro-osteodystrophy, thrombocytopenia-absent radius syndrome, fibular hemimelia, Larsen syndrome, and Williams-Beuren syndrome. 1,2,[3][4][5][6][7][8][9][10][11][12] Obligate dislocation is also associated with syndromes such as Down syndrome, Rubinstein-Taybi syndrome, nail-patella syndrome, Kabuki syndrome, and Ellis-Van Crevald syndrome. In these later syndromes, the patellar dislocation may occur after birth and can become permanent and irreducible during childhood.…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Congenital dislocation of the patella is associated with arthrogryposis, chondrodysplasia punctata, dyschondrosteosis, chondro-osteodystrophy, thrombocytopenia-absent radius syndrome, fibular hemimelia, Larsen syndrome, and Williams-Beuren syndrome. 1,2,[3][4][5][6][7][8][9][10][11][12] Obligate dislocation is also associated with syndromes such as Down syndrome, Rubinstein-Taybi syndrome, nail-patella syndrome, Kabuki syndrome, and Ellis-Van Crevald syndrome. In these later syndromes, the patellar dislocation may occur after birth and can become permanent and irreducible during childhood.…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
“…13 Regarding the laterality of this condition, numerous authors have reported that it can present either unilaterally or bilaterally. 2,12,19 Sever et al reported that upon review of the literature, there were 36 reported cases of bilateral involvement and 45 cases of unilateral involvement. 11 When patellar dislocation occurs with each flexionextension cycle of the knee, this is deemed habitual or obligate dislocation.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…CDP may occur as an isolated clinical entity or is associated with polymalformative syndrome. [ 4 , 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…CDP is characterized by stiffness, short quadriceps, femoropatellar dysplasia, flexion contracture, genu valgum, external tibial torsion, and foot deformities. CDP may occur as an isolated clinical entity or is associated with polymalformative syndrome [4,5] …”
Section: Introductionmentioning
confidence: 99%
“…Congenital patellar dislocation (CPD) is a highly rare condition, presenting as a manually irreducible lateral patellar bone dislocation with a flexion contracture and valgus tibial deviation [ 1 ]. It can simultaneously occur alongside other disorders such as Ellis-van Creveld syndrome, Down syndrome, and Rubinstein-Taybi syndrome [ 2 ].…”
Section: Introductionmentioning
confidence: 99%